Journey into America : The Challenge of Islam - Ahmed, Akbar S. (Book collections on Project MUSE., 2010)
"Examines American identity as influenced by its founding and history and the diverse Muslim experience in America, as well as the experience of other religious groups, and how each has affected the other"--Provided by publisher